Treatment of the «intra-abdominal infection» after orthotopic liver transplantation (a case report) - M. Sh. Khubutia; S. V. Zhuravel; N. K. Kuznetsova; M. S. Novruzbekov; A. O. Chugunov; I. V. Alexandrova (Трансплантология (Москва), 2018)
This article is аn example of a successful treatment intra-abdominal infection after liver transplantation.